Secondary prevention of early-onset sepsis: a less invasive Italian approach for managing neonates at risk. - Berardi, Alberto; Tzialla, Chryssoula; Travan, Laura; Bua, Jenny; Santori, Daniele; Azzalli, Milena; Spada, Caterina; Lucaccioni, Laura (Ital J Pediatr, 2018)
Strategies to prevent early-onset sepsis (EOS) have led to a substantial decline in many countries. However, one of the most controversial topics in neonatology is the management of asymptomatic full-term and late preterm neonates at risk for EOS, and guidelines lack substantial consensus regarding this issue. A strategy for managing neonates, entirely based on serial physical examinations, has been developed in two Italian regions. This strategy seems safe, while reducing laboratory tests and unnecessary antibiotics. In the current commentary we provide area-based data concerning the prevention of EOS in 2 northern Italian regions, and we detail the results of their strategy for managing healthy-appearing newborns at risk for EOS.

Serum Stem Cell Growth Factor Beta for the Prediction of Therapy Response in Hepatocellular Carcinoma. - Sukowati, Caecilia H C; Patti, Riccardo; Pascut, Devis; Ladju, Rusdina B; Tarchi, Paola; Zanotta, Nunzia; Comar, Manola; Tiribelli, Claudio; Crocè, Lory S (Biomed Res Int, 2018)
Introduction: Chronic inflammatory response is one of major contributors in the development of hepatocellular carcinoma (HCC). Inflammatory molecules, such as cytokines and growth factors in the circulation, can be useful in the diagnosis and prognosis of the patients. The stem cell growth factor beta (SCGF), a newly found protein, is a secreted sulfated glycoprotein and it functions as a growth factor for primitive hematopoietic progenitor cells. The level of SCGF had been reported to be elevated in several cancer types. However, there is very few or even no information on this protein in the study of HCC, even more in clinical studies. Methods: A multiplex immunoassay panel of 48 cytokines and growth factors were utilized to screen 68 sera from 29 HCC patients at pretreatment (T0), 1 month (T1), and 6 months (T6) after treatment by either radiofrequency ablation (RF) or transarterial chemoembolization (TACE). Treatment response was evaluated according to mRECIST criteria. Results: Immunoassay screening showed that the levels of IL-17, CTACK, TNF, IL-2R, IL-8, and SCGF were different in Complete Responders (CR) and Nonresponders (NR) groups. At T0 and T1, the SCGF level was significantly the highest in NR (23.8 and 40.7 ng/mL, respectively), followed by early recurrence (25.4 and 25.0 ng/mL), and CR (6.7 and 5.3 ng/mL), independently from HCV, stages, and treatment type. Low basal SCGF level was associated with longer disease-free survival compared to high SCGF. Conclusion: In this study, for the first time, we demonstrate that the high level of serum SCGF at pre- and posttreatment is associated with HCC nonresponsiveness.
Keywords: Aged; Carcinoma, Hepatocellular; Chemoembolization, Therapeutic; Female; Hematopoietic Cell Growth Factors; Humans; Liver Neoplasms; Male; Middle Aged; Neoplasm Recurrence, Local; Retrospective Studies; Stem Cells; Treatment Outcome

Safety and effectiveness of oral propranolol for infantile hemangiomas started before 5 weeks and after 5 months of age: an Italian multicenter experience. - El Hachem, Maya; Gesualdo, Francesco; Diociaiuti, Andrea; Berti, Irene; Vercellino, Nadia; Boccaletti, Valeria; Neri, Iria; Porcedda, Giulio; Greco, Antonella; Carnevale, Claudia; Oranges, Teresa; Cutrone, Mario; et al. (Ital J Pediatr, 2017)
BACKGROUND: Despite not being licensed for the treatment of infantile hemangiomas (IH) in infants younger than 5 weeks or older than 5 months, propranolol is often used in these age groups to prevent or to treat potentially severe complications. The objective of the present study was to review the experience of 8 Italian pediatric and dermatologic centers regarding propranolol treatment for IH started before 5 weeks or after 5 months of age. METHODS: We retrospectively reviewed the records of patients followed up for IH, on propranolol treatment started before 5 weeks or after 5 months of age, and collected information on sociodemographic data, treatment indications, IH involution, IH relapse, and treatment side effects. RESULTS: A total of 343 patients were enrolled; 15 were started on propranolol before 5 weeks (group 1), 328 were started after 5 months of age (group 2). The most frequent indications were permanent aesthetical disfigurement (91.8%) and function threatening complications (42.6%). In most cases, the treatment was effective. The involution was partial in 67.7% of patients. In 11.8% of cases a relapse was observed. No relapse was observed in group 1. Treatment complications were reported in 15.8% of children, most frequently sleep disorders (6.6%), followed by irritability (5.1%) and diarrhea (2.2%). Only a case of mild constipation was observed in group 1. CONCLUSION: The safety and effectiveness profile of propranolol in infants younger than 5 weeks or older than 5 months may be acceptable. Taking in account propranolol's potential in preventing severe complications, further studies should assess the acceptability of propranolol treatment, especially in the <5-week age group .
Keywords: Administration, Oral; Age Factors; Cohort Studies; Dose-Response Relationship, Drug; Drug Administration Schedule; Female; Hemangioma; Humans; Infant; Infant, Newborn; Italy; Male; Patient Safety; Propranolol; Retrospective Studies; Skin Neoplasms; Treatment Outcome

Shifts of subgingival bacterial population after nonsurgical and pharmacological therapy of localized aggressive periodontitis, followed for 1 year by Ion Torrent PGM platform. - Campisciano, Giuseppina; Toschetti, Annamaria; Comar, Manola; Taranto, Rosanna Di; Berton, Federico; Stacchi, Claudio (Eur J Dent, 2017)
The possibility of targeting the hypervariable region V3 of the 16S rRNA gene using Ion Torrent Personal Genome Machine (PGM) could provide a complete analysis of subgingival plaque samples, potentially able to identify microbiological species missed by culture-based methods. A 16-year-old female smoker patient, affected by localized aggressive periodontitis, underwent a full-mouth disinfection protocol and was inserted in a 3-month recall program. Microbiological samples were collected at baseline and at 30, 100, 365 days follow-up and analyzed by Ion Torrent PGM. , , , and were the most represented pathogens at baseline. Nonsurgical treatment and systemic antibiotics drastically lowered the anaerobic species, and their presence remained limited after 100 days, while a consistent recolonization by anaerobic bacteria was detected at 365 days. The patient showed a general improvement of periodontal conditions. Differently from polymerase chain reaction and other microarray techniques, Ion Torrent performs a quantitative analysis of the microbiota, irrespective of the searched species. An accurate definition of the shifts of the bacterial community might help periodontal researchers for a better understanding of the impact of different treatment approaches or in intercepting nonresponsive conditions.

Somatic symptom disorder was common in children and adolescents attending an emergency department complaining of pain. - Cozzi, Giorgio; Minute, Marta; Skabar, Aldo; Pirrone, Angela; Jaber, Mohamad; Neri, Elena; Montico, Marcella; Ventura, Alessandro; Barbi, Egidio (Acta Paediatr, 2017)
AIM: The aim of this study was to quantify the prevalence of somatic pain in a paediatric emergency department (ED). METHODS: We conducted a prospective observational study using patients admitted to the ED of an Italian children's hospital between December 2014 and February 2015. We enrolled children aged 7-17 who turned up at the ED complaining of pain. Patients and parents were asked to fill in a questionnaire to allow the analysis of the patients' medical history and provide contact details for follow-up. We divided the enrolled patients into four groups: post-traumatic pain, organic pain, functional pain and somatic pain. The questionnaire was used to define pain characteristics and to generate an impairment score. RESULTS: Of the 713 patients who met inclusion criteria, 306 (42.9%) were enrolled in the study. Of these, 135 (44.0%) suffered from post-traumatic pain, 104 (34.0%) from organic pain, 41 (13.4%) from functional pain and 26 (8.6%) from somatic pain. Somatic pain patients had endured pain longer, had missed more school days and had suffered severe functional impairment. CONCLUSION: This study highlighted that somatic pain was a significant contributor to paediatric emergency room visits and should be suspected and diagnosed in children reporting pain.
Keywords: Adolescent; Child; Emergency Service, Hospital; Female; Humans; Italy; Male; Medically Unexplained Symptoms; Pain; Prospective Studies

Subclinical alteration of the cervical-vaginal microbiome in women with idiopathic infertility. - Campisciano, Giuseppina; Florian, Fiorella; D'Eustacchio, Angela; Stanković, David; Ricci, Giuseppe; De Seta, Francesco; Comar, Manola (J Cell Physiol, 2017)
Biomarkers have a wide application in research and clinic, they help to choose the correct treatment for diseases. Recent studies, addressing the vaginal microbiome using next generation sequencing (NGS), reported the involvement of bacterial species in infertility. We compared the vaginal microbiome of idiopathic infertile women with that of healthy, including bacterial vaginosis affected women and non-idiopathic infertile women, to identify bacterial species suitable as biomarkers. Information on microorganisms was obtained from the V3-16S rDNA sequencing of cervical-vaginal fluids of 96 women using the Ion Torrent platform. Data were processed with QIIME and classified against the Vaginal 16S rDNA Reference Database. The analysis revealed a significant beta-diversity variation (p < 0.001) between the four groups included in the study. L. iners, L. crispatus, and L. gasseri distinguished idiopathic infertile women from the other groups. In these women, a microbial profile similar to that observed in bacterial vaginosis women has been detected. Our results suggest that the quantitative assessment and identification of specific microorganisms of the cervical-vaginal microflora could increase the accuracy of available tools for the diagnosis of infertility and improve the adoption of therapeutic protocols.
Keywords: Adult; Biodiversity; Cervix Uteri; Cohort Studies; Demography; Female; Humans; Infertility, Female; Microbiota; Species Specificity; Vagina; Vaginosis, Bacterial

Subcutaneous Granuloma Annulare: A Diagnostic Conundrum-Learning From Mistakes. - Pederiva, Federica; Paloni, Giulia; Berti, Irene (Pediatr Emerg Care, 2017)
Subcutaneous granuloma annulare is an inflammatory lesion occurring in otherwise healthy children. We present 3 pediatric patients with different diagnostic-therapeutic paths depending on the ward they were referred to. The lesions regress spontaneously, and medical or surgical treatments are generally not necessary.
Keywords: Arm; Child, Preschool; Connective Tissue Diseases; Diagnosis, Differential; Female; Granuloma Annulare; Humans; Infant; Leg; Male; Ultrasonography, Doppler, Color

Surgery for distal hypospadias: what about the catheter? - Scarpa, Maria-Grazia; Perin, Giordano; Di Grazia, Massimo; Codrich, Daniela; Pederiva, Federica; Guida, Edoardo; Lembo, Maria Antonietta; Giannotta, Antonio; Schleef, Jurgen (Pediatr Med Chir, 2017)
No agreed recommendations exist for timing of urethral stent removal, after distal hypospadias surgery. We compared our preliminary case series with outcomes from literature: 18/44 patients were treated with catheter and 26/44 without it. The surgical outcome was comparable in the two groups. After hypospadias surgery, the main advantage of the immediate postoperative catheter removal was the shorter hospital stay without negatively affecting the care and home management.
Keywords: Child; Child, Preschool; Device Removal; Humans; Hypospadias; Infant; Length of Stay; Male; Retrospective Studies; Stents; Treatment Outcome; Urinary Catheterization

SV40 Infection of Mesenchymal Stromal Cells From Wharton's Jelly Drives the Production of Inflammatory and Tumoral Mediators. - Cason, Carolina; Campisciano, Giuseppina; Zanotta, Nunzia; Valencic, Erica; Delbue, Serena; Bella, Ramona; Comar, Manola (J Cell Physiol, 2017)
The Mesenchymal Stromal Cells from umbilical cord Wharton's jelly (WJSCs) are a source of cells with high potentiality for the treatment of human immunological disorders. Footprints of the oncogenic viruses Simian Virus 40 (SV40) and JC Virus (JCPyV) have been recently detected in human WJSCs specimens. The aim of this study is to evaluate if WJSCs can be efficiently infected by these Polyomaviruses and if they can potentially exert tumoral activity. Cell culture experiments indicated that WJSCs could sustain both SV40 and JCPyV infections. A transient and lytic replication was observed for JCPyV, while SV40 persistently infected WJSCs over a long period of time, releasing a viral progeny at low titer without evident cytopathic effect (CPE). Considering the association between SV40 and human tumors and the reported ability of the oncogenic viruses to drive the host innate immune response to cell transformation, the expression profile of a large panel of immune mediators was evaluated in supernatants by the Bioplex platform. RANTES, IL-3, MIG, and IL-12p40, involved in chronic inflammation, cells differentiation, and transformation, were constantly measured at high concentration comparing to control. These findings represent a new aspect of SV40 biological activity in the humans, highlighting its interaction with specific host cellular pathways. In view of these results, it seems to be increasingly urgent to consider Polyomaviruses in the management of WJSCs for their safely use as promising therapeutic source. J. Cell. Physiol. 232: 3060-3066, 2017. © 2016 Wiley Periodicals, Inc.
Keywords: Cell Line, Transformed; Cell Separation; Cell Transformation, Viral; Chemokine CCL5; Chemokine CXCL9; Cytopathogenic Effect, Viral; DNA, Viral; Host-Pathogen Interactions; Humans; Inflammation Mediators; Interleukin-12 Subunit p40; Interleukin-3; JC Virus; Mesenchymal Stem Cells; Real-Time Polymerase Chain Reaction; Simian virus 40; Time Factors; Up-Regulation; Viral Load; Virus Replication; Wharton Jelly

Synthesis of Lipophilic Core-Shell FeO@SiO@Au Nanoparticles and Polymeric Entrapment into Nanomicelles: A Novel Nanosystem for in Vivo Active Targeting and Magnetic Resonance-Photoacoustic Dual Imaging. - Monaco, Ilaria; Arena, Francesca; Biffi, Stefania; Locatelli, Erica; Bortot, Barbara; La Cava, Francesca; Marini, Giada Maria; Severini, Giovanni Maria; Terreno, Enzo; Comes Franchini, Mauro (Bioconjug Chem, 2017)
In this work, iron/silica/gold core-shell nanoparticles (FeO@SiO@Au NPs) characterized by magnetic and optical properties have been synthesized to obtain a promising theranostic platform. To improve their biocompatibility, the obtained multilayer nanoparticles have been entrapped in polymeric micelles, decorated with folic acid moieties, and tested in vivo for photoacoustic and magnetic resonance imaging detection of ovarian cancer.
Keywords: Animals; Cell Proliferation; Female; Ferric Compounds; Folic Acid; Gold; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Magnetite Nanoparticles; Mice; Mice, Inbred BALB C; Mice, Nude; Micelles; Multimodal Imaging; Ovarian Neoplasms; Photoacoustic Techniques; Polymers; Silicon Dioxide; Tumor Cells, Cultured; Xenograft Model Antitumor Assays

"Safety and utility of percutaneous liver biopsy in hematopoietic stem cell transplant pediatric recipients: a retrospective study". - Maximova, Natalia; Gregori, Massimo; Barbieri, Francesca; Pizzol, Antonio; Sonzogni, Aurelio (BMC Cancer, 2016)
BACKGROUND: Liver biopsies in pediatric hematopoietic stem cell transplantation (HSCT) patients are as and effective when performed at bedside in the Bone Marrow Transplant Unit (BMTU) than in the Day Surgery Unit (DSU), with better patient compliance and lower emotional distress for these children. METHODS: The study group consisted of 45 children who underwent allogeneic HSCT. We reviewed 68 liver biopsies performed between April 2006 and September 2015. 12 (17.6 %) biopsies were performed in the DSU and 56 (82.3 %) in the BMTU; nine (13.2 %) prior to HSCT and 59 (86.7 %) after HSCT. Pre-procedural behavioral status (subjective score) was evaluated by pediatric transplant physicians by filling in a questionnaire employing a three-point scale: "calm and cooperative", "agitated and non-cooperative" or "frightened and suffering". Objective score was obtained measuring patient's heart rate before the procedure and comparing it with mean heart rate. RESULTS: Patients who underwent the procedure at the BMTU experienced less emotional distress than those who underwent it in the DSU: 58.3 % of patients treated at the DSU were agitated as compared with 16.1 % of those treated at the BMTU (p < 0.01). Among the 59 biopsies performed after HSCT, 41 (69.5 %) were taken from symptomatic patients for a diagnostic purpose and 18 (30.5 %) in asymptomatic ones in order to rule out hepatic GVHD. Among these 18 procedures, GVHD was diagnosed in 16 (88.9 %) cases. Minor complications occurred in about 17 % of procedures (12 biopsies), at a rate of 25 % for the DSU location compared with 16 % for the BMTU location. Only two major complications were reported, one in the DSU and one in the BMTU. CONCLUSION: Liver biopsy performed at bedside in HSCT patients does not carry a higher risk of adverse events than the same procedure performed in the DSU and has lower emotional distress associated with better patient compliance, thus contributing significantly to a higher standard of care.

Snakin: Structure, Roles and Applications of a Plant Antimicrobial Peptide. - Oliveira-Lima, Marx; Benko-Iseppon, Ana Maria; Neto, José Ribamar Costa Ferreira; Rodríguez-Decuadro, Susana; Kido, Éderson Akio; Crovella, Sergio; Pandolfi, Valesca (Curr Protein Pept Sci, 2016)
Snakins are plant antimicrobial peptides (AMPs) of the Snakin/GASA family, formed by three distinct regions: an N-terminal signal peptide; a variable site; and the GASA domain in the C-terminal region composed by twelve conserved cysteine residues that contribute to the biochemical stability of the molecule. These peptides are known to play different roles in response to a variety of biotic (i.e. induced by bacteria, fungi and nematode pathogens) and abiotic (salinity, drought and ROS) stressors, as well as in crosstalk promoted by plant hormones, with emphasis on abscisic and salicylic acid (ABA and SA, respectively). Such properties make snakin/GASA members promising biotechnological sources for potential therapeutic and agricultural applications. However, information regarding their tertiary structure, mode of action and function are not yet completely elucidated. The present review presents aspects of snakin structure, expression, functional studies and perspectives about the potential applications for agricultural and medical purposes.

Somatic, hematologic phenotype, long-term outcome, and effect of hematopoietic stem cell transplantation. An analysis of 97 Fanconi anemia patients from the Italian national database on behalf of the Marrow Failure Study Group of the AIEOP (Italian Associ - Svahn, Johanna; Bagnasco, Francesca; Cappelli, Enrico; Onofrillo, Daniela; Caruso, Silvia; Corsolini, Fabio; De Rocco, Daniela; Savoia, Anna; Longoni, Daniela; Pillon, Marta; Marra, Nicoletta; Ramenghi, Ugo; et al. (Am J Hematol, 2016)
We analyzed 97 Fanconi anemia patients from a clinic/biological database for genotype, somatic, and hematologic phenotype, adverse hematological events, solid tumors, and treatment. Seventy-two patients belonged to complementation group A. Eighty percent of patients presented with mild/moderate somatic phenotype and most with cytopenia. No correlation was seen between somatic/hematologic phenotype and number of missense mutations of FANCA alleles. Over follow-up, 33% of patients improved or maintained mild/moderate cytopenia or normal blood count, whereas remaining worsened cytopenia. Eleven patients developed a hematological adverse event (MDS, AML, pathological cytogenetics) and three developed solid tumors. 10 years cumulative risk of death of the whole cohort was 25.6% with median follow-up 5.8 years. In patients eligible to hematopoietic stem cell transplantation because of moderate cytopenia, mortality was significantly higher in subjects transplanted from matched unrelated donor over nontransplanted subjects, whereas there was no significant difference between matched sibling donor transplants and nontransplanted patients. In patients eligible to transplant because of severe cytopenia and clonal disease, mortality risk was not significantly different in transplanted from matched unrelated versus matched sibling donor versus nontransplanted subjects. The decision to transplant should rely on various elements including, type of donor, HLA matching, patient comorbidities, impairment, and clonal evolution of hematopoiesis. Am. J. Hematol. 91:666-671, 2016. © 2016 Wiley Periodicals, Inc.

A Spotted Bone. - Perin, Silvia; Rabach, Ingrid; Pascolo, Paola; Dibello, Daniela; Ventura, Alessandro (J Pediatr, 2016)

Synchrotron X-ray microscopy reveals early calcium and iron interaction with crocidolite fibers in the lung of exposed mice. - Pascolo, Lorella; Zabucchi, Giuliano; Gianoncelli, Alessandra; Kourousias, George; Trevisan, Elisa; Pascotto, Ernesto; Casarsa, Claudia; Ryan, Chris; Lucattelli, Monica; Lungarella, Giuseppe; Cavarra, Eleonora; Bartalesi, Barbara; et al. (Toxicol Lett, 2016)
Human exposure to asbestos can cause a wide variety of lung diseases that are still a current major health concern, even if asbestos has been banned in many countries. It has been shown in many studies that asbestos fibers, ingested by alveolar macrophages, disrupt lung iron homeostasis by sequestering iron. Calcium can also be deposited on the fibers. The pathways along which iron and above all calcium interact with fibers are still unknown. Our aim was that of investigating if the iron accumulation induced by the inhaled asbestos fibers also involves calcium ions accumulation. Lung sections of asbestos-exposed mice were analyzed using an extremely sensitive procedure available at the synchrotron facilities, that provides morphological and chemical information based on X-ray fluorescence microspectroscopy (μ-XRF). In this study we show that (1) where conventional histochemical procedures revealed only weak deposits of iron and calcium, μ-XRF analysis is able to detect significant deposits of both iron and calcium on the inhaled asbestos fibers; (2) the extent of the deposition of these ions is proportionally directly related and (3) iron and calcium deposition on inhaled asbestos fibers is concomitant with the appearance of inflammatory and hyperplastic reactions.

A Sensitive Electrochemiluminescence Immunosensor for Celiac Disease Diagnosis Based on Nanoelectrode Ensembles. - Habtamu, Henok B; Sentic, Milica; Silvestrini, Morena; De Leo, Luigina; Not, Tarcisio; Arbault, Stephane; Manojlovic, Dragan; Sojic, Neso; Ugo, Paolo (Anal Chem, 2015)

Sensorineural hearing loss in very low birth weight infants with histological chorioamnionitis. - Vedovato, Stefania; Lo Iacono, Angela; Morando, Carla; Suppiej, Agnese; Orzan, Eva; Trevisanuto, Daniele; Visentin, Silvia; Cavallin, Francesco; Chiarelli, Silvia; Zanardo, Vincenzo (J Matern Fetal Neonatal Med, 2015)
OBJECTIVE: Histological chorioamnionitis (HCAM) has been associated with inflammatory diseases of preterm infants. Recently we have observed that it increased the risk of speech delay and hearing loss. So the aim of this study was to evaluate the relationship between sensorineural hearing loss (SNHL) of VLBW infants and HCAM. METHODS: We performed an observational study on VLBW infants admitted to the NICU of Padua. Each patient with HCAM was matched with one control without HCAM. All infants underwent hearing screening before discharge by means of automated transient-evoked otoacustic emissions and automated auditory brainstem responses, which were repeated at 3 and 6 months of age with tympanometry measurement. Incidence of SNHL at 6 months of age was compared in the 2 groups and risk factors for hearing loss were studied. RESULTS: Two of 77 (2.6%) newborns with HCAM e 6/73 (8.2%) without it presented SNHL at 6 months of corrected age (p = 0.16). Multivariable logistic regression analysis identified surgical ligation of patent ductus arteriosus (PDA) as independent predictors of SNHL (OR: 5.75, 95% CI 1.34-24.84, p = 0.02), whereas the effect of HCAM on SNHL was only near to statistical significance level. CONCLUSIONS: Surgical ligation of PDA is associated with an increased risk of SNHL in VLBW infants, regardless of HCAM.

Serum anti-tissue transglutaminase antibodies detected during febrile illness may not be produced by the intestinal mucosa. - De Leo, Luigina; Quaglia, Sara; Ziberna, Fabiana; Vatta, Serena; Martelossi, Stefano; Maschio, Massimo; Not, Tarcisio (J Pediatr, 2015)
Anti-transglutaminase antibodies are the diagnostic marker of celiac disease, and are considered to be synthesized only by intestinal B-lymphocytes. During an infectious disease, these antibodies are transiently detected in serum. We show that these infection-triggered antibodies may not originate in the intestinal mucosa and are not an indication of celiac disease.
Keywords: Autoantibodies; Celiac Disease; Child, Preschool; Diagnosis, Differential; Enzyme-Linked Immunosorbent Assay; Female; GTP-Binding Proteins; Humans; Intestinal Mucosa; Male; Transglutaminases

Serum TRAIL levels increase shortly after insulin therapy and metabolic stabilization in children with type 1 diabetes mellitus. - Tornese, Gianluca; Tisato, Veronica; Monasta, Lorenzo; Vecchi Brumatti, Liza; Zauli, Giorgio; Secchiero, Paola (Acta Diabetol, 2015)

A Shining Scrotal Fountain. - Copertino, Marco; Benelli, Elisa; Gregori, Massimo; Barbi, Egidio; Ventura, Alessandro (J Pediatr, 2015)
Keywords: Child; Edema; Humans; Male; Penile Diseases; Scrotum

Short Communication FYB polymorphisms in Brazilian patients with type I diabetes mellitus and autoimmune polyglandular syndrome type III. - Addobbati, C J C; de Azevêdo Silva, J; Tavares, N A C; Araujo, J; Guimarães, R L; Brandão, L; Crovella, S; Sandrin-Garcia, P (Genet Mol Res, 2015)
The aim of this study was to perform an association study between seven Fyn-binding protein gene (FYB)-tag single nucleotide polymorphisms (SNPs) and type I diabetes mellitus (T1DM), as well as with disease age of onset. We also assessed the role of FYB SNPs in the insurgence of autoimmune polyglandular syndrome type III (APSIII), characterized by the simultaneous presence of autoimmune thyroid disease and celiac disease, in patients with T1DM from a Northeastern Brazilian population. One hundred and seventy-seven patients with T1DM and 190 healthy individuals were genotyped for seven tag SNPs, covering most of the FYB locus, using real-time polymerase chain reaction amplification. There was no significant difference in the distribution of allele and genotype frequencies among patients and healthy individuals. Moreover, none of the tag SNPs were associated either to T1DM age of onset or to the insurgence of APSIII. However, since the FYB protein is a key component in T cell response, its gene variants might play a role in protein function, which might be testable in a population with different genetic backgrounds or by using functional assays.

Sirolimus Therapy in Congenital Hyperinsulinism: A Successful Experience Beyond Infancy. - Minute, Marta; Patti, Giuseppa; Tornese, Gianluca; Faleschini, Elena; Zuiani, Chiara; Ventura, Alessandro (Pediatrics, 2015)
Congenital hyperinsulinism (CHI) due to diffuse involvement of the pancreas is a challenging and severe illness in children. Its treatment is based on chronic therapy with diazoxide and/or octreotide, followed by partial pancreatectomy, which is often not resolutive. Sirolimus, a mammalian target of rapamycin inhibitor, was reported to be effective in treating CHI in infants. We report here the case of an 8-year-old boy affected by a severe form of CHI due to a biallelic heterozygous ABCC8 mutation who responded to sirolimus with a dramatic improvement in his glucose blood level regulation and quality of life, with no serious adverse events after 6 months of follow-up. To the best of our knowledge, this is the first report of a successful intervention in an older child. It provides a promising basis for further studies comparing sirolimus with other treatments, particularly in older children.

Splenic Infarction in Acute Infectious Mononucleosis. - Naviglio, Samuele; Abate, Maria Valentina; Chinello, Matteo; Ventura, Alessandro (J Emerg Med, 2015)
BACKGROUND: The evaluation of a febrile patient with acute abdominal pain represents a frequent yet possibly challenging situation in the emergency department (ED). Splenic infarction is an uncommon complication of infectious mononucleosis, and may have a wide range of clinical presentations, from dramatic to more subtle. Its pathogenesis is still incompletely understood, yet it may be associated with the occurrence of transient prothrombotic factors. CASE REPORT: We report the case of a 14-year-old boy who presented with fever, sore throat, left upper quadrant abdominal pain, and splenomegaly, with no history of recent trauma. Laboratory tests revealed a markedly prolonged activated partial thromboplastin time and positive lupus anticoagulant. Abdominal ultrasonography showed several hypoechoic areas in the spleen consistent with multiple infarctions. Magnetic resonance imaging eventually confirmed the diagnosis. He was admitted for observation and supportive treatment, and was discharged in good condition after 7 days. WHY SHOULD AN EMERGENCY PHYSICIAN BE AWARE OF THIS?: Spontaneous splenic infarction should be considered in the differential list of patients presenting with left upper quadrant abdominal pain and features of infectious mononucleosis; the diagnosis, however, may not be straightforward, as clinical presentation may also be subtle, and abdominal ultrasonography, which is often used as a first-line imaging modality in pediatric EDs, has low sensitivity in this scenario and may easily miss it. Furthermore, although treatment is mainly supportive, close observation for possible complications is necessary.

Subcutaneous panniculitis-like T-cell lymphoma presenting with diffuse cutaneous edema in a 2-year-old child. - Chinello, Matteo; Naviglio, Samuele; Remotti, Daniele; Locasciulli, Anna; Ventura, Alessandro (J Pediatr Hematol Oncol, 2015)
Keywords: Child, Preschool; Edema; Humans; Lymphoma, T-Cell; Male; Panniculitis; Skin Diseases

Salt-inducible kinase 3, SIK3, is a new gene associated with hearing. - Wolber, Lisa E; Girotto, Giorgia; Buniello, Annalisa; Vuckovic, Dragana; Pirastu, Nicola; Lorente-Cánovas, Beatriz; Rudan, Igor; Hayward, Caroline; Polasek, Ozren; Ciullo, Marina; Mangino, Massimo; Steves, Claire; et al. (Hum Mol Genet, 2014)
Hearing function is known to be heritable, but few significant and reproducible associations of genetic variants have been identified to date in the adult population. In this study, genome-wide association results of hearing function from the G-EAR consortium and TwinsUK were used for meta-analysis. Hearing ability in eight population samples of Northern and Southern European ancestry (n = 4591) and the Silk Road (n = 348) was measured using pure-tone audiometry and summarized using principal component (PC) analysis. Genome-wide association analyses for PC1-3 were conducted separately in each sample assuming an additive model adjusted for age, sex and relatedness of subjects. Meta-analysis was performed using 2.3 million single-nucleotide polymorphisms (SNPs) tested against each of the three PCs of hearing ability in 4939 individuals. A single SNP lying in intron 6 of the salt-inducible kinase 3 (SIK3) gene was found to be associated with hearing PC2 (P = 3.7×10(-8)) and further supported by whole-genome sequence in a subset. To determine the relevance of this gene in the ear, expression of the Sik3 protein was studied in mouse cochlea of different ages. Sik3 was expressed in murine hair cells during early development and in cells of the spiral ganglion during early development and adulthood. Our results suggest a developmental role of Sik3 in hearing and may be required for the maintenance of adult auditory function.
Keywords: Age Factors; Animals; Cochlea; European Continental Ancestry Group; Genome-Wide Association Study; Hearing; Humans; Mice, Inbred C57BL; Polymorphism, Single Nucleotide; Protein Kinases

The second generation of HIV-1 vertically exposed infants: a case series from the Italian Register for paediatric HIV infection. - Calitri, Carmelina; Gabiano, Clara; Galli, Luisa; Chiappini, Elena; Giaquinto, Carlo; Buffolano, Wilma; Genovese, Orazio; Esposito, Susanna; Bernardi, Stefania; de Martino, Maurizio; Tovo, Pier-Angelo (BMC Infect Dis, 2014)
BACKGROUND: In the Highly Active Antiretroviral Therapy (HAART) era, the prognosis of children perinatally infected with HIV-1 has significantly improved, so the number of perinatally-infected females entering child-bearing age and experiencing motherhood is increasing. METHODS: A description of the medical history and pregnancy outcomes of women with perinatal acquired HIV-1 infection enrolled in the Italian Register for HIV infection in Children. RESULTS: Twenty-three women had 29 pregnancies. They had started an antiretroviral therapy at a median of 7.7 years (interquartile range, IQR 2.3 - 11.4), and had experienced a median of 4 therapeutic regimens (IQR 2-6). Twenty women (87%) had taken zidovudine (AZT) before pregnancy, in 14 cases as a starting monotherapy. In 21 pregnancies a protease inhibitor-based regimen was used. At delivery, the median of CD4+ T lymphocytes was 450/μL (IQR 275-522), and no viral load was detectable in 15 cases (reported in 21 pregnancies). Twenty-eight children were delivered through caesarean section (median gestational age: 38 weeks, IQR 36-38, median birth weight: 2550 grams, IQR 2270 - 3000). Intravenous AZT was administered during delivery in 26 cases. All children received oral AZT (median: 42 days, IQR 31 - 42), with no adverse events reported. No child acquired HIV-1 infection. CONCLUSIONS: Despite a long history of maternal infection, multiple antiretroviral regimens and, perhaps, the development of drug-resistant viruses, the risk of mother-to-child transmission does not seem to have increased among the second-generation of HIV-1 exposed infants.
Keywords: Adult; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; Birth Weight; Cesarean Section; Child; Female; HIV Infections; HIV-1; Humans; Infant; Infectious Disease Transmission, Vertical; Italy; Male; Pediatrics; Pregnancy; Pregnancy Complications, Infectious; Pregnancy Outcome; Prospective Studies; Viral Load; Young Adult; Zidovudine

Serum amyloid protein A concentration in cryopyrin-associated periodic syndromes patients treated with interleukin-1 beta antagonist. - Pastore, Serena; Paloni, Giulia; Caorsi, Roberta; Ronfani, Luca; Taddio, Andrea; Lepore, Loredana (Clin Exp Rheumatol, 2014)
OBJECTIVES: Cryopyrin-associated periodic syndromes (CAPS) are a group of chronic, relapsing autoinflammatory disorders which may be complicated by systemic AA amyloidosis. The aim of our study was to evaluate serum amyloid protein A (SAA) level in CAPS patients treated with Interleukin-1beta (IL-1β) antagonist and to correlate its level with treatment response. METHODS: All patients of CAPS Italian Register treated with IL-1β inhibitor were enrolled. SAA levels before starting therapy, and at last visit were evaluated. Patients were then divided in complete responders and partial responders. RESULTS: Twenty-five patients were enrolled. SAA level before starting therapy was increased (median 118.5 mg/L, IQR 96.4-252.8; normal value <6.4 mg/L), while at last visit SAA was significantly reduced (median 4.3 mg/L, IQR 2.3-12.7) (p<0.001). However 12 patients still presented SAA levels beyond normal range, 10/25 patients (40%) showed a complete response to treatment. Conversely, 15 patients presented only a partial response, of which 12 for increased SAA value and 3 for increased CRP value. Patients with partial response had SAA values significantly higher than patients with complete response (median 12.6 mg/L; IQR 8.3-20.0 vs. 2.7 mg/L; IQR 1.6-4.1, p<0.001). CONCLUSIONS: Our results confirm the long term efficacy of anti IL-1β treatment in CAPS and the decrease of SAA levels; however 48% of patients still presented SAA elevation despite treatment. The real risk of these patients in developing amyloidosis is not clear but the persistent increase of SAA needs a close follow-up.
Keywords: Adolescent; Adult; Amyloidosis; Child; Child, Preschool; Cryopyrin-Associated Periodic Syndromes; Drug Monitoring; Female; Humans; Immunosuppressive Agents; Interleukin-1beta; Male; Middle Aged; Serum Amyloid A Protein; Treatment Outcome; Young Adult

Severe inflammatory bowel disease associated with congenital alteration of transforming growth factor beta signaling. - Naviglio, Samuele; Arrigo, Serena; Martelossi, Stefano; Villanacci, Vincenzo; Tommasini, Alberto; Loganes, Claudia; Fabretto, Antonella; Vignola, Silvia; Lonardi, Silvia; Ventura, Alessandro (J Crohns Colitis, 2014)
Transforming growth factor beta is a pleiotropic cytokine which plays a central role in the homeostasis of the immune system. A complex dysregulation of its signaling occurs in Loeys-Dietz syndrome, a monogenic disorder caused by mutations of transforming growth factor beta receptors type 1 or type 2, characterized by skeletal involvement, craniofacial abnormalities, and arterial tortuosity with a strong predisposition for aneurysm and dissection. In addition, several immunologic abnormalities have been described in these patients, including an increased risk of allergic disorders as well as eosinophilic gastrointestinal disorders. The occurrence of inflammatory bowel disorders has been also reported, but it is poorly documented. We describe two unrelated children with Loeys-Dietz syndrome affected by severe chronic inflammatory colitis appearing at an early age. The intestinal disease presented similar features in both patients, including a histopathological picture of non-eosinophilic chronic ulcerative colitis, striking elevation of inflammatory markers, and a distinctly severe clinical course leading to failure to thrive, with resistance to multiple immunosuppressive treatments. One of the patients also presented autoimmune thyroiditis. Our report confirms that chronic ulcerative colitis may be associated with Loeys-Dietz syndrome. This finding suggests that an alteration of transforming growth factor beta signaling may by itself predispose to inflammatory colitis in humans, and represent an invaluable model to understand inflammatory bowel diseases.
Keywords: Child, Preschool; Colon; Colonoscopy; Female; Humans; Infant; Inflammatory Bowel Diseases; Loeys-Dietz Syndrome; Male; Signal Transduction; Transforming Growth Factor beta

Severe neonatal hyperbilirubinemia and UGT1A1 promoter polymorphism. - Travan, Laura; Lega, Sara; Crovella, Sergio; Montico, Marcella; Panontin, Elisa; Demarini, Sergio (J Pediatr, 2014)
OBJECTIVE: To assess whether UGT1A1 promoter polymorphisms associated with Gilbert Syndrome (GS) occur with a greater frequency in neonates with severe hyperbilirubinemia. STUDY DESIGN: In a case-control study performed at a single hospital center in Italy, 70 case subjects with severe hyperbilirubinemia (defined as bilirubin level ≥20 mg/dL or 340 μmol/L) and 70 controls (bilirubin level <12 mg/dL or 210 μmol/L) were enrolled. Both case and control subjects were full term newborns. Polymerase chain reaction analysis on blood spot was performed to determine the frequency of UGTA1A1 promoter polymorphisms in cases and controls. RESULTS: No statistical difference in the prevalence of UGTA1A1 gene variants was found between cases and controls (P = 1). Thirteen infants homozygous for (TA)7 polymorphism associated with GS were in the case group (18.6%) and 14 in the control group (20.0%). A heterozygous group was also equally distributed between cases (44.3%) and controls (42.9%). No (TA)8 repeat was found in the 2 groups. CONCLUSIONS: In our study population, GS polymorphism alone does not appear to play a major role in severe neonatal hyperbilirubinemia in neonates without signs of hemolysis.
Keywords: Case-Control Studies; Female; Genotype; Gilbert Disease; Glucuronosyltransferase; Humans; Hyperbilirubinemia, Neonatal; Infant, Newborn; Male; Polymerase Chain Reaction; Polymorphism, Genetic; Prevalence; Promoter Regions, Genetic

Short communication: novel truncating mutations in the CFTR gene causing a severe form of cystic fibrosis in Italian patients. - Lenarduzzi, S; Morgutti, M; Crovella, S; Coiana, A; Rosatelli, M C (Genet Mol Res, 2014)
Cystic fibrosis (CF) is a common recessive genetic disease caused by mutations in the gene encoding for the cystic fibrosis transmembrane conductance regulator (CFTR) protein. More than 1800 different mutations have been described to date. Here, we report 3 novel mutations in CFTR in 3 Italian CF patients. To detect and identify 36 frequent mutations in Caucasians, we used the INNO-LiPA CFTR19 and INNO-LiPA CFTR17+Tn Update kits (Innogenetics; Ghent, Belgium). Our first analysis did not reveal both of the responsible mutations; thus, direct sequencing of the CFTR gene coding region was performed. The 3 patients were compound heterozygous. In one allele, the F508del (c.1521_1523delCTT, p.PHE508del) mutation in exon 11 was observed in each case. For the second allele, in patient No.1, direct sequencing revealed an 11-base pair deletion (GAGGCGATACT) in exon 14 (c.2236_2246del; pGlu746Alafs*29). In patient No. 2, direct sequencing revealed a nonsense mutation at nucleotide 3892 (c.3892G>T) in exon 24. In patient No. 3, direct sequencing revealed a deletion of cytosine in exon 27 (c.4296delC; p.Asn1432Lysfs*16). These 3 novel mutations indicate the production of a truncated protein, which consequently results in a non-functional polypeptide.
Keywords: Alleles; Base Sequence; Cystic Fibrosis; Cystic Fibrosis Transmembrane Conductance Regulator; DNA Mutational Analysis; Exons; Female; Heterozygote; Humans; Infant; Infant, Newborn; Italy; Molecular Sequence Data; Mutation; Open Reading Frames; Severity of Illness Index

Single-day trimethoprim/sulfamethoxazole prophylaxis for Pneumocystis pneumonia in children with cancer. - Caselli, Désirée; Petris, Maria Grazia; Rondelli, Roberto; Carraro, Francesca; Colombini, Antonella; Muggeo, Paola; Ziino, Ottavio; Melchionda, Fraia; Russo, Giovanna; Pierani, Paolo; Soncini, Elena; DeSantis, Raffaella; et al. (J Pediatr, 2014)
OBJECTIVE: To determine whether a simplified, 1-day/week regimen of trimethoprim/sulfamethoxazole is sufficient to prevent Pneumocystis (jirovecii [carinii]) pneumonia (PCP). Current recommended regimens for prophylaxis against PCP range from daily administration to 3 consecutive days per week dosing. STUDY DESIGN: A prospective survey of the regimens adopted for the PCP prophylaxis in all patients treated for childhood cancer at pediatric hematology-oncology centers of the Associazione Italiana Ematologia Oncologia Pediatrica. RESULTS: The 20 centers participating in the study reported a total of 2466 patients, including 1093 with solid tumor and 1373 with leukemia/lymphoma (or primary immunodeficiency; n = 2). Of these patients, 1371 (55.6%) received the 3-day/week prophylaxis regimen, 406 (16.5%) received the 2-day/week regimen, and 689 (27.9%), including 439 with leukemia/lymphoma, received the 1-day/week regimen. Overall, only 2 cases of PCP (0.08%) were reported, both in the 2-day/week group. By intention to treat, the cumulative incidence of PCP at 3 years was 0.09% overall (95% CI, 0.00-0.40%) and 0.51% for the 2-day/week group (95% CI, 0.10%-2.00%). Remarkably, both patients who failed had withdrawn from prophylaxis. CONCLUSION: A single-day course of prophylaxis with trimethoprim/sulfamethoxazole may be sufficient to prevent PCP in children with cancer undergoing intensive chemotherapy regimens. This simplified strategy might have implications for the emerging need for PCP prophylaxis in other patients subjected to the increased use of biological and nonbiological agents that induce higher levels of immune suppression, such as those with rheumatic diseases.
Keywords: Anti-Infective Agents; Child; Dose-Response Relationship, Drug; Drug Administration Schedule; Follow-Up Studies; Hematologic Neoplasms; Humans; Incidence; Italy; Pneumocystis carinii; Pneumonia, Pneumocystis; Prospective Studies; Treatment Outcome; Trimethoprim, Sulfamethoxazole Drug Combination

Sodium dichloroacetate exhibits anti-leukemic activity in B-chronic lymphocytic leukemia (B-CLL) and synergizes with the p53 activator Nutlin-3. - Agnoletto, Chiara; Melloni, Elisabetta; Casciano, Fabio; Rigolin, Gian Matteo; Rimondi, Erika; Celeghini, Claudio; Brunelli, Laura; Cuneo, Antonio; Secchiero, Paola; Zauli, Giorgio (Oncotarget, 2014)
The anti-leukemic activity of the mitochondria-targeting small molecule sodium dichloroacetate (DCA), used alone and in association with the small molecule inhibitor of the p53/MDM2 interaction Nutlin-3, was analyzed in primary B-chronic lymphocytic leukemia (B-CLL) samples (n=22), normal peripheral blood cells (n=10) and in p53wild-type EHEB, JVM-2, JVM-3 B lymphoblastoid cell lines. DCA exhibited a dose-dependent anti-leukemic activity in both primary B-CLL and B leukemic cell lines with a functional p53 status and showed a synergistic cytotoxic activity when used in combination with Nutlin-3. At the molecular level, DCA positively regulated p53 activity, as documented by post-transcriptional modifications of p53 protein and synergized with Nutlin-3 in increasing the expression of the p53-target genes MDM2, PUMA, TIGAR and in particular p21. The potential role of p21 in mediating the DCA+Nutlin-3 anti-leukemic activity was underscored in knocking-down experiments. Indeed, transfection of leukemic cells with p21 siRNAs significantly decreased the DCA+Nutlin-3-induced cytotoxicity. Taken together, our data emphasize that DCA is a molecule that merits to be further evaluated as a chemotherapeutic agent for B-CLL, likely in combination with other therapeutic compounds.
Keywords: Aged; Aged, 80 and over; Dichloroacetic Acid; Drug Synergism; Female; Humans; Imidazoles; Leukemia, Lymphocytic, Chronic, B-Cell; Male; Middle Aged; Piperazines; Tumor Suppressor Protein p53

Soluble TRAIL is present at high concentrations in seminal plasma and promotes spermatozoa survival. - Zauli, Giorgio; Celeghini, Claudio; Monasta, Lorenzo; Martinelli, Monica; Luppi, Stefania; Gonelli, Arianna; Grill, Vittorio; Ricci, Giuseppe; Secchiero, Paola (Reproduction, 2014)
The expression of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL(TNFSF10)) and of its receptors (TRAILR1, TRAILR2, TRAILR3, and TRAILR4) have been documented in testis, but the presence of soluble TRAIL in seminal fluid, as well as the potential physiopathological role of the TRAIL/TRAILR system in spermatozoa, has not been previously investigated. Male donors (n=123) among couples presenting for infertility evaluation were consecutively enrolled in this study. The presence of soluble TRAIL was analyzed in seminal samples by ELISA, while the surface expression of TRAIL receptors was investigated by flow cytometry. High levels of soluble TRAIL were detected in seminal plasma (median, 11 621 pg/ml and mean±s.d., 13 371±8367 pg/ml) and flow cytometric analysis revealed a variable expression of TRAIL receptors in the sperm cellular fraction among different subjects. In addition, the effect of physiologically relevant concentrations of recombinant TRAIL was investigated on survival and motility of spermatozoa. Of interest, the in vitro exposure of capacitated spermatozoa to recombinant TRAIL (10 ng/ml) significantly preserved their overall survival. Therefore, the present study demonstrates for the first time the presence of elevated levels of the anti-inflammatory cytokine TRAIL in seminal fluids. Moreover, the demonstration that recombinant TRAIL promotes spermatozoa survival after capacitation suggests potential therapeutic implications.
Keywords: Adult; Apoptosis; Enzyme-Linked Immunosorbent Assay; Flow Cytometry; Humans; Infertility, Male; Male; Receptors, TNF-Related Apoptosis-Inducing Ligand; Semen; Sperm Capacitation; Sperm Motility; Spermatozoa; TNF-Related Apoptosis-Inducing Ligand

Spectrum of the mutations in Bernard-Soulier syndrome. - Savoia, Anna; Kunishima, Shinji; De Rocco, Daniela; Zieger, Barbara; Rand, Margaret L; Pujol-Moix, Núria; Caliskan, Umran; Tokgoz, Huseyin; Pecci, Alessandro; Noris, Patrizia; Srivastava, Alok; Ward, Christopher; et al. (Hum Mutat, 2014)
Bernard-Soulier syndrome (BSS) is a rare autosomal recessive bleeding disorder characterized by defects of the GPIb-IX-V complex, a platelet receptor for von Willebrand factor (VWF). Most of the mutations identified in the genes encoding for the GP1BA (GPIbα), GP1BB (GPIbβ), and GP9 (GPIX) subunits prevent expression of the complex at the platelet membrane or more rarely its interaction with VWF. As a consequence, platelets are unable to adhere to the vascular subendothelium and agglutinate in response to ristocetin. In order to collect information on BSS patients, we established an International Consortium for the study of BSS, allowing us to enrol and genotype 132 families (56 previously unreported). With 79 additional families for which molecular data were gleaned from the literature, the 211 families characterized so far have mutations in the GP1BA (28%), GP1BB (28%), or GP9 (44%) genes. There is a wide spectrum of mutations with 112 different variants, including 22 novel alterations. Consistent with the rarity of the disease, 85% of the probands carry homozygous mutations with evidence of founder effects in some geographical areas. This overview provides the first global picture of the molecular basis of BSS and will lead to improve patient diagnosis and management.
Keywords: Alleles; Bernard-Soulier Syndrome; Databases, Nucleic Acid; Founder Effect; Genetic Variation; Humans; Mutation; Platelet Glycoprotein GPIb-IX Complex; Polymorphism, Single Nucleotide; von Willebrand Diseases; Web Browser

Systemic Lupus Erythematosus: Old and New Susceptibility Genes versus Clinical Manifestations. - J, De Azevêdo Silva; C, Addobbati; P, Sandrin-Garcia; S, Crovella (Curr Genomics, 2014)
Systemic Lupus Erythematosus (SLE) is one of the most relevant world-wide autoimmune disorders. The formation of autoantibodies and the deposition of antibody-containing immune complexes in blood vessels throughout the body is the main pathogenic mechanism of SLE leading to heterogeneous clinical manifestations and target tissue damage. The complexity of etiology and pathogenesis in SLE, enclosing genetic and environmental factors, apparently is one of the greatest challenges for both researchers and clinicians. Strong indications for a genetic background in SLE come from studies in families as well as in monozygotic and dizygotic twins, discovering several SLE-associated loci and genes (e.g. IRF5, PTPN22, CTLA4, STAT4 and BANK1). As SLE has a complex genetic background, none of these genes is likely to be entirely responsible for triggering autoimmune response in SLE even if they disclosure a potentially novel molecular mechanisms in the pathogenesis' disease. The clinical manifestations and disease severity varies greatly among patients, thus several studies try to associate clinical heterogeneity and prognosis with specific genetic polymorphisms in SLE associated genes. The continue effort to describe new predisposing or modulating genes in SLE is justified by the limited knowledge about the pathogenesis, assorted clinical manifestation and the possible prevention strategies. In this review we describe newly discovered, as well as the most studied genes associated to SLE susceptibility, and relate them to clinical manifestations of the disease.

Safety and efficacy of infliximab and adalimumab for refractory uveitis in juvenile idiopathic arthritis: 1-year followup data from the Italian Registry. - Zannin, Maria E; Birolo, Carolina; Gerloni, Valeria M; Miserocchi, Elisabetta; Pontikaki, Irene; Paroli, Maria P; Bracaglia, Claudia; Shardlow, Alison; Parentin, Fulvio; Cimaz, Rolando; Simonini, Gabriele; Falcini, Fernanda; et al. (J Rheumatol, 2013)
OBJECTIVE: To evaluate safety and efficacy of adalimumab (ADA) and infliximab (IFX) for the treatment of juvenile idiopathic arthritis-related anterior uveitis (JIA-AU). METHODS: Starting January 2007, patients with JIA-AU treated with IFX and ADA were managed by a standard protocol and data were entered into the National Italian Registry (NIR). At baseline, all patients were refractory to standard immunosuppressive treatment and/or were corticosteroid-dependent. Data recorded every 3 months included uveitis course, number/type of ocular complications, drug-related adverse events (AE), treatment change or withdrawal, and laboratory measures. Data of patients treated for at least 1 year were retrieved from the NIR and analyzed using descriptive statistics. Treatment efficacy was based on change in uveitis course and in number of ocular complications. RESULTS: Up to December 2009, data for 108 patients with JIA-AU treated with anti-tumor necrosis factor-α agents were recorded in the NIR and data from 91, with at least 12 months' followup, were included in the study. Forty-eight patients were treated with IFX, 43 with ADA. Forty-seven patients (55.3%) achieved remission of AU, 28 (32.9%) had recurrent AU, and 10 (11.8%) maintained a chronic course. A higher remission rate was observed with ADA (67.4% vs 42.8% with IFX; p = 0.025). Ocular complications decreased from 0.47 to 0.32 per subject. Five patients experienced resolution of structural complications. No patient reported serious AE; 8 (8.8%) experienced 11 minor AE (9 with IFX, 2 with ADA). CONCLUSION: IFX and ADA appear to be effective and safe for treatment of refractory JIA-related uveitis, with a better performance of ADA in the medium-term period.
Keywords: Adolescent; Antibodies, Monoclonal; Antibodies, Monoclonal, Humanized; Antirheumatic Agents; Arthritis, Juvenile; Child; Child, Preschool; Female; Follow-Up Studies; Humans; Infant; Italy; Male; Registries; Treatment Outcome; Tumor Necrosis Factor-alpha; Uveitis

Sedation with intranasal midazolam of Angolan children undergoing invasive procedures. - Kawanda, Lumana; Capobianco, Ivan; Starc, Meta; Felipe, Daniel; Zanon, Davide; Barbi, Egidio; Munkela, Nadine; Rodrigues, Verónica; Malundo, Lúis; Not, Tarcisio (Acta Paediatr, 2012)
AIM: Ambulatory surgery is a daily requirement in poor countries, and limited means and insufficient trained staff lead to the lack of attention to the patient's pain. Midazolam is a rapid-onset, short-acting benzodiazepine which is used safely to reduce pain in children. We evaluated the practicability of intranasal midazolam sedation in a suburban hospital in Luanda (Angola), during the surgical procedures. METHODS: Intranasal midazolam solution was administered at a dose of 0.5 mg/kg. Using the Ramsay's reactivity score, we gave a score to four different types of children's behaviour: moaning, shouting, crying and struggling, and the surgeon evaluated the ease of completing the surgical procedure using scores from 0 (very easy) to 3 (managing with difficulty). RESULTS: Eighty children (median age, 3 years) were recruited, and 140 surgical procedures were performed. Fifty-two children were treated with midazolam during 85 procedures, and 28 children were not treated during 55 procedures. We found a significant difference between the two groups on the shouting, crying and struggling parameters (p < 0.001). The mean score of the ease of completing the procedures was significantly different among the two groups (p < 0.0001). CONCLUSION: These results provide a model of procedural sedation in ambulatory surgical procedures in poor countries, thus abolishing pain and making the surgeon's job easier.
Keywords: Administration, Intranasal; Adolescent; Ambulatory Surgical Procedures; Angola; Child; Child Behavior; Child, Preschool; Conscious Sedation; Crying; Female; Humans; Hypnotics and Sedatives; Infant; Male; Midazolam; Prospective Studies

Serum amyloid A and cholesterol: a pivotal role on inflammation. - Tricarico, Paola Maura; Marcuzzi, Annalisa; Zanin, Valentina; Kleiner, Giulio; Bianco, Anna Monica; Crovella, Sergio (Amyloid, 2012)
Keywords: Animals; Humans; Serum Amyloid A Protein

Sexually transmitted infections and diseases: old and new challenges - part I - Introduction. - Guaschino, S; Zuccati, G (G Ital Dermatol Venereol, 2012)
Keywords: Humans; Sexually Transmitted Diseases

Should cardiac involvement be included in the criteria for diagnosis of Churg Strauss syndrome? - Amaddeo, Alessandro; Ventura, Alessandro; Marchetti, Federico; Benettoni, Alessandra; Londero, Margherita (J Pediatr, 2012)
Keywords: Adolescent; Churg-Strauss Syndrome; Heart Diseases; Humans; Male

Simian virus 40 efficiently infects human T lymphocytes and extends their lifespan. - Mazzoni, Elisa; Rigolin, Gian Matteo; Alaribe, Franca Nneka; Pancaldi, Cecilia; Maniero, Stefania; Comar, Manola; Martini, Fernanda; Tognon, Mauro (Exp Hematol, 2012)
The relevance of viral infections to the onset and progression of human hematologic malignancies and other blood diseases is still a matter of active investigation. Purified human T lymphocytes isolated from the peripheral blood mononuclear cells of healthy blood donors were experimentally infected with simian virus 40 (SV40), a small DNA tumor virus. SV40-positive T lymphocytes extended their lifespan up to day 80 postinfection (PI). Expression of viral antigens, such as the large T antigen and the viral capsid protein VP1 from the early and late regions, respectively, was detected up to day 40 PI. SV40 viral progeny were continuously produced from day 10 to 40 PI. SV40 DNA sequences were detected in infected T cells for up to 80 days. Our data indicate that human T lymphocytes can be efficiently infected with SV40. Although T cells infected by SV40 were not immortalized, 30% of these lymphocytes appeared to be morphologically transformed with an enlarged T-cell shape. Our investigation provides a simple model for studying the interactions of human T lymphocytes with this small DNA tumor virus and it might represent an experimental tool for investigating new biomarkers and targets for innovative therapeutic approaches.
Keywords: Antigens, Polyomavirus Transforming; Cell Line, Transformed; Cell Survival; Humans; Microscopy, Electron, Transmission; Simian virus 40; T-Lymphocytes

Simultaneous determination of multiple cytokines reveals a pro-inflammatory and pro-angiogenic signature after major cardiothoracic surgery: potential role of C-reactive protein. - Tisato, Veronica; Monasta, Lorenzo; Biolo, Gianni; Donatelli, Francesco; Secchiero, Paola; Zauli, Giorgio (Cytokine, 2012)
Keywords: C-Reactive Protein; Coronary Artery Bypass; Cytokines; Humans; Inflammation; Macrophages; Neovascularization, Physiologic; Risk Factors

Slow growth: do not forget the thyroid. - Tornese, Gianluca; Tonini, Giorgio; Ventura, Alessandro (J Pediatr Gastroenterol Nutr, 2012)
Keywords: Constipation; Female; Humans; Hypothyroidism; Male; Thyroid Function Tests

SOCS1 is significantly up-regulated in Nutlin-3-treated p53wild-type B chronic lymphocytic leukemia (B-CLL) samples and shows an inverse correlation with miR-155. - di Iasio, Maria Grazia; Norcio, Alessia; Melloni, Elisabetta; Zauli, Giorgio (Invest New Drugs, 2012)
The basal SOCS1 mRNA levels were significantly lower in p53(mutated) BJAB and MAVER leukemic cell lines with respect to p53(wild-type) SKW6.4 and JVM-2 leukemic cell lines, p53(wild-type) primary B chronic lymphocytic leukemia (B-CLL) cells and primary normal peripheral blood mononuclear cells (PBMC). Moreover, the MDM2 small molecule inhibitor Nutlin-3 significantly increased the levels of SOCS1 mRNA in both primary p53(wild-type) B-CLL cells as well as in p53(wild-type) B leukemic cell lines, but not in p53(mutated) B leukemic cell lines nor in primary PBMC. Of note, a significant inverse correlation was observed between SOCS1 mRNA and miR-155 levels in Nutlin-3-treated primary B-CLL cells and PBMC, suggesting that the miRNA-155/SOCS1 axis represents a potentially important therapeutic target of Nutlin-3 in B-CLL.
Keywords: Cell Line, Tumor; Cells, Cultured; Down-Regulation; Humans; Imidazoles; Leukemia, Lymphocytic, Chronic, B-Cell; Leukocytes, Mononuclear; MicroRNAs; Piperazines; Suppressor of Cytokine Signaling Proteins; Tumor Suppressor Protein p53; Up-Regulation

Soluble TRAIL is elevated in recurrent miscarriage and inhibits the in vitro adhesion and migration of HTR8 trophoblastic cells. - Agostinis, Chiara; Bulla, Roberta; Tisato, Veronica; De Seta, Francesco; Alberico, Salvatore; Secchiero, Paola; Zauli, Giorgio (Hum Reprod, 2012)
STUDY QUESTION: What is the potential physiopathological role of tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) in recurrent miscarriage (RM), characterized by at least three consecutive pregnancy losses. SUMMARY ANSWER: The levels of serum TRAIL immediately after miscarriage in RM patients are significantly elevated with respect to that in first-trimester normal pregnant women, and recombinant TRAIL inhibits the adhesion and migration of HTR8 trophoblastic cells in vitro. WHAT IS KNOWN ALREADY: Both TRAIL and its trans-membrane receptors (TRAIL-R1, TRAIL-R2, TRAIL-R3 and TRAIL-R4) have been documented in the placenta, but their physiopathological role is incompletely understood. STUDY DESIGN, SIZE, DURATION: The study populations consisted of RM patients (n = 80) and first-trimester normal pregnant women (n = 80). Blood samples were obtained within 24 h after abortion (RM) or at gestational 12-week (normal pregnant women). As additional controls, third-trimester normal pregnant women (n = 28) were examined before (within 72 h) and after (within 24 h) partum. PARTICIPANTS/MATERIALS, SETTING, METHODS: The concentrations of TRAIL were analysed in serum samples by ELISA. In parallel, the effect of soluble recombinant TRAIL (0.1-1000 ng/ml) was analysed on the survival of primary extravillus trophoblasts (EVTs) and on the survival, proliferation, adhesion and migration of trophoblastic HTR8 cells. MAIN RESULTS AND THE ROLE OF CHANCE: The circulating levels of TRAIL in RM women (median: 52.5 pg/ml; mean and SD: 55.5 ± 24.4 pg/ml) were significantly higher with respect to first-trimester normal pregnant women (median: 44.9 pg/ml; mean and SD: 47 ± 15.1 pg/ml) and third-trimester normal pregnant women, as assessed before (median: 45.1 pg/ml; mean and SD: 46 ± 12.4 pg/ml) and after partum (median: 35.4 pg/ml; mean and SD: 38 + 17.5 pg/ml). Both primary EVT and HTR8 cells expressed detectable levels of TRAIL death receptors, but exposure to soluble recombinant TRAIL did not induce cell death of trophoblastic cells. On the other hand, TRAIL dose-dependently inhibited the adhesion of HTR8 cells to decidual endothelial cells (DEC) as well as the migration of HTR8 in transwell assays using either fibronectin or DEC. LIMITATIONS, REASONS FOR CAUTION: Although this study suggests that TRAIL might have a pathogenic role in RM by inhibiting both the adhesion and migration capabilities of first trimester trophoblastic cells, there is a possibility that the elevated serum levels of TRAIL in RM are not cause but rather the result of RM. WIDER IMPLICATIONS OF THE FINDINGS: Our current findings together with data of other authors suggest that circulating TRAIL should be further analysed as a potential important biomarker in different physiopathological settings. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by FIRB projects (RBAP11Z4Z9_002 to Giorgio Zauli and RBAP10447J_002 to Paola Secchiero). The authors have no competing interests to declare.
Keywords: Abortion, Habitual; Apoptosis; Cell Adhesion; Cell Line; Cell Movement; Cells, Cultured; Enzyme-Linked Immunosorbent Assay; Female; Humans; Pregnancy; Receptors, TNF-Related Apoptosis-Inducing Ligand; TNF-Related Apoptosis-Inducing Ligand; Trophoblasts

The sorafenib plus nutlin-3 combination promotes synergistic cytotoxicity in acute myeloid leukemic cells irrespectively of FLT3 and p53 status. - Zauli, Giorgio; Celeghini, Claudio; Melloni, Elisabetta; Voltan, Rebecca; Ongari, Manuele; Tiribelli, Mario; di Iasio, Maria Grazia; Lanza, Francesco; Secchiero, Paola (Haematologica, 2012)
BACKGROUND: Both the multi-kinase inhibitor sorafenib and the small molecule inhibitor of the MDM2/p53 interaction, nutlin-3, used alone, have shown promising anti-leukemic activity in acute myeloid leukemia cells. Thus, in this study we investigated the effect of the combination of sorafenib plus nutlin-3 in acute myeloid leukemia. DESIGN AND METHODS: Primary acute myeloid leukemia blasts (n=13) and FLT3(wild-type)/p53(wild-type) (OCI-AML3), FLT3(mutated)/p53(wild-type) (MOLM), FLT3(mutated)/p53(mutated) (MV4-11), FLT3(wild-type)/p53(deleted) (HL60) or FLT3(wild-type)/p53(mutated) (NB4) acute myeloid cell lines were exposed to sorafenib, used alone or in association with nutlin-3 at a 1:1 ratio, in a range of clinically achievable concentrations (1-10 μM). Induction of apoptosis and autophagy was evaluated by transmission electron microscopy and by specific flow cytometry analyses. The levels of Mcl-1, p53 and Bak proteins were analyzed by western blotting. Knock-down of Bax and Bak gene expression was performed in transfection experiments with specific short interfering RNA. RESULTS: The sorafenib+nutlin-3 drug combination exhibits synergistic cytotoxicity in primary acute myeloid leukemia blasts and in acute myeloid leukemia cell lines with maximal cytotoxicity in FLT3(mutated) MV4-11 and MOLM, followed by the FLT3(wild-type) OCI-AML3, HL60 and NB4 cell lines. The cytotoxic activity of sorafenib+nutlin-3 was characterized by an increase of both apoptosis and autophagy. Moreover, Bax and Bak showed prominent roles in mediating the decrease of cell viability in response to the drug combination in p53(wild-type) OCI-AML3 and p53(deleted) HL-60 cells, respectively, as demonstrated in transfection experiments performed with specific short interfering RNA. CONCLUSIONS: Our data demonstrate that acute myeloid leukemia cells show a variable but overall good susceptibility to the innovative therapeutic combination of sorafenib+nutlin-3, which differentially involves the pro-apoptotic Bcl-2 family members Bax and Bak in p53(wild-type) and p53(deleted) cells.
Keywords: Antineoplastic Agents; Drug Synergism; Female; fms-Like Tyrosine Kinase 3; HL-60 Cells; Humans; Imidazoles; Leukemia, Myeloid, Acute; Male; Niacinamide; Phenylurea Compounds; Piperazines; Tumor Suppressor Protein p53

Specific protein profile in cerebrospinal fluid from HIV-1-positive cART-treated patients affected by neurological disorders. - Zanin, Valentina; Delbue, Serena; Marcuzzi, Annalisa; Tavazzi, Eleonora; Del Savio, Rossella; Crovella, Sergio; Marchioni, Enrico; Ferrante, Pasquale; Comar, Manola (J Neurovirol, 2012)
Cytokines/chemokines are involved in the immune response of infections, including HIV-1. We defined the profile of 48 cytokines/chemokines in cerebrospinal fluid from 18 cART patients with chronic HIV-1 infection by Luminex technology. Nine patients were affected with leukoencephalopathies: five with John Cunningham virus (JCV) + progressive multifocal leukoencephalopathy (PML) and four with JCV-not determined leukoencephalopathy (NDLE). In addition, nine HIV-1-positive patients with no neurological signs (NND) and five HIV-1-negative patients affected with acute disseminated encephalomyelitis (ADEM) were enrolled. Ten cytokines (IL-15, IL-3, IL-16, IL-18, CTACK, GRO1, SCF, MCP-1, MIF, SDF) were highly expressed in HIV-1-positive patients while IL-1Ra and IL-17 were present at a lower level. In addition, the levels of IL-17, IL-9, FGF-basic, MIP-1β, and MCP-1 were significantly higher (p < 0.05) in patients with neurological diseases (PML, NDLE, ADEM) with respect to NND. Focusing the attention to the cytokine profile in JCV + PML patients with respect to JCV-NDLE patients, only TNF-β was significantly downregulated (p < 0.05) in JCV + PML patients. This pilot study emphasized the role of immunoregulation in HIV-1-related neurological disorders during cART treatment.
Keywords: Adult; Aged; Anti-HIV Agents; Cytokines; Encephalomyelitis, Acute Disseminated; Female; HIV Infections; HIV-1; Humans; Leukoencephalopathy, Progressive Multifocal; Male; Middle Aged; Pilot Projects

State of art and recent developments of anti-cancer strategies based on TRAIL. - Bernardi, Stella; Secchiero, Paola; Zauli, Giorgio (Recent Pat Anticancer Drug Discov, 2012)
Multicellular organisms require apoptosis whereby the human body eliminates unnecessary and/or damaged cells. Apoptosis, or programmed cell death, can indeed be considered as a constitutive anti-cancer mechanism that seems to be defective in more than 50% of cancers. Molecular insights on the biology of the apoptotic process have led to the development of new anti-cancer strategies aiming at recovering and stimulating this process. Preclinical and clinical studies of our and other groups have demonstrated that targeting the extrinsic apoptotic pathway by various death receptors agonists is a safe and effective anti-cancer strategy, which thus may become a new cornerstone of cancer therapy. Here, we review the most recent acquisitions and patents on TRAIL or TRAIL mimetics, as well as the combination therapies that could be used with them.
Keywords: Animals; Antineoplastic Agents; Antineoplastic Combined Chemotherapy Protocols; Apoptosis; Clinical Trials as Topic; Humans; Mice; Neoplasms; Receptors, Death Domain; TNF-Related Apoptosis-Inducing Ligand

State of the art of the therapeutic perspective of sorafenib against hematological malignancies. - Zauli, G; Voltan, R; Tisato, V; Secchiero, P (Curr Med Chem, 2012)
The bi-aryl urea multi-kinase inhibitor Sorafenib (BAY 43-9006, Nexavar) was initially approved for the treatment of unresectable hepatocellular carcinoma and advanced renal cell carcinoma. Eleven years after its first description in PubMed, the therapeutic potential of Sorafenib has been evaluated in an increasing number of studies, mainly focused on solid tumors. More recently, the potential usefullness of Sorafenib has started to emerge also against hematological malignancies. At the molecular level, besides the RAF kinase pathway, which represents the first therapeutic target of Sorafenib, additional kinases, in particular the vascular endothelial growth factor receptor, have been identified as important targets of Sorafenib. A great interest for the potential use of Sorafenib against acute myeloid leukemia (AML) arose when it was demonstrated that a specific mutation of a kinase gene, called FMS-like tyrosin-kinase-3- internal tandem duplication (FLT-3-ITD) and occurring in more than 30% of AML, represents a molecular target of Sorafenib. However, recent phase I and II clinical studies showed that, in spite of its ability to suppress the activity of this mutated kinase, resistence to Sorafenib rapidly occurs in AML, suggesting that Sorafenib will be more effective in combined therapy than used as single drug. Another critical molecular target of Sorafenib is the anti-apoptotic protein Mcl-1. The ability of Sorafenib to rapidly shut-off Mcl-1 in virtually all the hematological malignancies investigated, including the B-chronic lymphocytic leukemia, represents a key element for its antileukemic activity as well as for therapeutic combinations based on Sorafenib. In this respect, it is of particular interest that many chemotherapeutic drugs or innovative anti-neoplastic compounds, such as recombinant TRAIL or inibitors of MDM2 protein, are either unable to down-regulate Mcl-1 or in some instances promote a paradoxical induction of Mcl-1. In this review, the growing evidences for the role of Mcl-1 in mediating the anti-leukemic activity of Sorafenib will be discussed in relationship with promising therapeutic perspectives.
Keywords: Apoptosis; Clinical Trials as Topic; fms-Like Tyrosine Kinase 3; Hematologic Neoplasms; Humans; Leukemia, Myeloid, Acute; Myeloid Cell Leukemia Sequence 1 Protein; Niacinamide; Phenylurea Compounds; Proto-Oncogene Proteins c-bcl-2; Proto-Oncogene Proteins c-mdm2; Receptors, Vascular Endothelial Growth Factor; TNF-Related Apoptosis-Inducing Ligand

Stem cell ageing and apoptosis. - Fulle, Stefania; Centurione, Lucia; Mancinelli, Rosa; Sancilio, Silvia; Manzoli, Francesco Antonio; Di Pietro, Roberta (Curr Pharm Des, 2012)
Ageing has been defined as the process of deterioration of many body functions over the lifespan of an individual. In spite of the number of different theories about ageing, there is a general consensus in identifying ageing effects in a reduced capacity to regenerate injured tissues or organs and an increased propensity to infections and cancer. In recent years the stem cell theory of ageing has gained much attention. Adult stem cells residing in mammalian tissues are essential for tissue homeostasis and repair throughout adult life. With advancing age, the highly regulated molecular signalling necessary to ensure proper cellular, tissue, and organ homeostasis loses coordination and leads, as a consequence, to a compromised potential of regeneration and repair of damaged cells and tissues. Although a complete comprehension of the molecular mechanisms involved in stem cell ageing and apoptosis is far to be reached, recent studies are beginning to unravel the processes involved in stem cell ageing, particularly in adult skeletal muscle stem cells, namely satellite cells. Thus, the focus of this review is to analyse the relationship between stem cell ageing and apoptosis with a peculiar attention to human satellite cells as compared to haematopoietic stem cells. Undoubtedly, the knowledge of age-related changes of stem cells will help in understanding the ageing process itself and will provide novel therapeutic challenges for improved tissue regeneration.
Keywords: Adult; Apoptosis; Cell Aging; Humans; Stem Cells

Stem cells in severe infantile spinal muscular atrophy (SMA1). - Carrozzi, Marco; Amaddeo, Alessandro; Biondi, Andrea; Zanus, Caterina; Monti, Fabrizio; Alessandro, Ventura (Neuromuscul Disord, 2012)
Keywords: Humans; Spinal Muscular Atrophies of Childhood; Stem Cell Transplantation; Stem Cells; Treatment Outcome

The submerged dyslexia iceberg: how many school children are not diagnosed? Results from an Italian study. - Barbiero, Chiara; Lonciari, Isabella; Montico, Marcella; Monasta, Lorenzo; Penge, Roberta; Vio, Claudio; Tressoldi, Patrizio Emanuele; Ferluga, Valentina; Bigoni, Anna; Tullio, Alessia; Carrozzi, Marco; Ronfani, Luca (PLoS One, 2012)
BACKGROUND: Although dyslexia is one of the most common neurobehavioral disorders affecting children, prevalence is uncertain and available data are scanty and dated. The objective of this study is to evaluate the prevalence of dyslexia in an unselected school population using clearly defined and rigorous diagnostic criteria and methods. METHODS: Cross sectional study. We selected a random cluster sample of 94 fourth grade elementary school classes of Friuli Venezia Giulia, a Region of North Eastern Italy. We carried out three consecutive levels of screening: the first two at school and the last at the Neuropsychiatry Unit of a third level Mother and Child Hospital. The main outcome measure was the prevalence of dyslexia, defined as the number of children positive to the third level of screening divided by the total number of children enrolled. RESULTS: We recruited 1774 children aged 8-10 years, of which 1528 received parents' consent to participate. After applying exclusion criteria, 1357 pupils constituted the final working sample. The prevalence of dyslexia in the enrolled population ranged from 3.1% (95% CI 2.2-4.1%) to 3.2% (95% CI 2.4-4.3%) depending on different criteria adopted. In two out of three children with dyslexia the disorder had not been previously diagnosed. CONCLUSIONS: This study shows that dyslexia is largely underestimated in Italy and underlines the need for reliable information on prevalence, in order to better allocate resources both to Health Services and Schools.
Keywords: Area Under Curve; Child; Cross-Sectional Studies; Delayed Diagnosis; Dyslexia; Female; Humans; Italy; Male; Neuropsychological Tests; Prevalence; Questionnaires; ROC Curve

Successful induction of oral tolerance in Netherton syndrome. - Pastore, Serena; Gorlato, Gaia; Berti, Irene; Barbi, Egidio; Ventura, Alessandro (Allergol Immunopathol (Madr), 2012)
Keywords: Allergens; Alopecia; Child, Preschool; Desensitization, Immunologic; Disease-Free Survival; Eczema; Female; Food Hypersensitivity; Hair Follicle; Humans; Immune Tolerance; Immunoglobulin E; Infant, Newborn; Mouth; Netherton Syndrome; Treatment Outcome

Safety and efficacy of high-dose acarbose treatment for dumping syndrome. - De Cunto, Angela; Barbi, Egidio; Minen, Federico; Ventura, Alessandro (J Pediatr Gastroenterol Nutr, 2011)
Dumping syndrome (DS) is a complication of Nissen fundoplication. Dietary strategies can ameliorate symptoms, but this approach is not always foolproof. Limited evidence reports the efficacy of acarbose for children who are unresponsive to feeding manipulations. We report 8 patients with DS aged between 7 and 24 months. In 4 of 8 nutritional strategies failed, and acarbose treatment was started. The initial dose was 25 mg for meals, and increased until postprandial glucose was stable. In 3 of 4 children the final dose was higher than previously reported, without adverse effects. Acarbose is useful to treat DS in cases of failure of dietary strategies.
Keywords: Acarbose; Child, Preschool; Dumping Syndrome; Female; Humans; Hyperglycemia; Hypoglycemic Agents; Infant; Male; Postprandial Period; Treatment Outcome

Secondary lymphoid tissue as an important site for WU polyomavirus infection in immunocompetent children. - Comar, Manola; Zanotta, Nunzia; Rossi, Tatiana; Pelos, Giorgio; D'Agaro, Pierlanfranco (J Med Virol, 2011)
The polyomaviruses KI and WU (KIPyV and WUPyV) have been identified in respiratory specimens from children with acute respiratory infections, which suggests the respiratory tract as a possible site of infection. However, the persistence of infection in the lymphoid system is unknown. Fresh samples (n = 211) of tonsils, adenoids, and peripheral blood mononuclear cells (PBMCs) from 83 immunocompetent children (mean age 4.8 years) were tested for amplification of the KIPyV VP1 and WUPyV VP2 genes. The known BK and JC polyomaviruses and the lymphotropic human herpesvirus (HHV)-6 were also investigated by quantitative real-time PCR and direct sequencing. In addition, 98 nasopharyngeal swabs collected from children (mean age 6.2 years) affected by seasonal influenza-like illness were tested. Of the lymphoid tissues, 34.9% were positive for WUPyV, 4.8% for BK virus, and 33.8% for HHV-6. KIPyV and JC virus were not detected in these specimens. None of the polyomaviruses were detected in PBMCs. Among the nasopharyngeal samples, the prevalence of WUPyV was 27.5%, although 70% of the positive samples were co-infected with at least one of the following respiratory viruses: influenza virus, adenovirus, and respiratory syncytial virus. Phylogenetic analysis revealed high sequence homology (99%) between lymphoid- and nasopharynx-derived WUPyV strains. These results suggest that the tonsils and adenoids of immunocompetent children are a reservoir for WUPyV infection; probably due to the respiratory route of transmission. In addition, the prevalence of WUPyV was high among the children, and the virus was identified more frequently in older children than during the first years of life.
Keywords: Adenoids; Child; Child, Preschool; DNA, Viral; Female; Humans; Infant; Leukocytes, Mononuclear; Male; Nasopharynx; Palatine Tonsil; Phylogeny; Polymerase Chain Reaction; Polyomavirus; Polyomavirus Infections; Prevalence; Sequence Analysis, DNA; Sequence Homology

Serum anti-Müllerian hormone as a predictive marker of polycystic ovarian syndrome. - Parco, Sergio; Novelli, Caterina; Vascotto, Fulvia; Princi, Tanja (Int J Gen Med, 2011)
BACKGROUND: The anti-Müllerian hormone (AMH) is a dimeric protein secreted by the female ovaries and has two fundamental roles in follicle genesis. It delays the entrance of the primordial follicle into the pool of follicles in growth and diminishes the sensitivity of the ovarian follicle towards follicle-stimulating hormone (FSH). The purpose of this work was to study the AMH (nv 2.0-6.8 ng/mL) as a marker during assisted reproductive technology (ART), in order to identify cases of infertility due to polycystic ovarian syndrome (PCOS). This syndrome affects 10% of women with infertility problems, and a new biological marker could be useful to general practitioners of internal medicine to help generate the suspicion of PCOS so that they can refer the patient to the gynecologist for confirmation. METHODS: This study enrolled 236 patients aged 26-46 years undergoing assisted reproductive technology at the Institute for Maternal and Child Health, Trieste, Italy. On the third day of the ovarian cycle, the patients were given doses of AMH, FSH, and luteinizing hormone (LH, in cases of AMH < 2.0-6.8 ng/mL). A control pelvic ultrasound was also carried out. RESULTS: We identified 57 patients who were starting in vitro fertilization or embryo transfer with AMH values within the normal range (3.64 ± 1.51 ng/mL), 77 with values below normal (1.38 ± 0.32 ng/mL), and 96 cases with undetectable values of AMH. Six patients had very high AMH levels (10.0 ± 2.28 ng/mL) and, of these, five were found to have PCOS on pelvic ultrasound examination (P < 0.05). We also found inverse correlations between AMH levels and age (r = -0.52) and between AMH and FSH levels (r = -0.32). CONCLUSION: In clinical practice it is common to encounter patients who turn to medicine in search of a cure for female infertility. In our experience, AMH two or three times the normal amount (10 ± 2.28 ng/mL), is a good indication of PCOS and infertility.

Setting research priorities to reduce global mortality from childhood pneumonia by 2015. - Rudan, Igor; El Arifeen, Shams; Bhutta, Zulfiqar A; Black, Robert E; Brooks, Abdullah; Chan, Kit Yee; Chopra, Mickey; Duke, Trevor; Marsh, David; Pio, Antonio; Simoes, Eric A F; Tamburlini, Giorgio; et al. (PLoS Med, 2011)
Keywords: Biomedical Research; Child, Preschool; Humans; Infant; Infant, Newborn; Pneumonia

Shwachman-Diamond syndrome and type 1 diabetes mellitus: more than a chance association? - Gana, S; Sainati, L; Frau, M R; Monciotti, C; Poli, F; Cannioto, Z; Comelli, M; Danesino, C; Minelli, A (Exp Clin Endocrinol Diabetes, 2011)
Shwachman-Diamond syndrome is a rare clinical condition consisting of exocrine pancreatic dysfunction, various degree of pancytopenia, and metaphyseal dysplasia. The majority of Shwachman-Diamond syndrome cases result from mutations in the Shwachman-Bodian-Diamond Syndrome gene. To date, type 1 diabetes mellitus has only been reported in 4 independent cases presenting with Shwachman-Diamond syndrome, 3 of them with molecular confirmation of the diagnosis. We describe 2 unrelated patients with clinical and molecular features typical of Shwachman-Diamond syndrome and type 1 diabetes mellitus. In addition, we report the occurrence rate of type 1 diabetes mellitus in the Italian registry for Shwachman-Diamond syndrome, which is low (3.23%) but increased at least 30-fold over the type 1 diabetes mellitus occurrence rate in the general population. No evidence of a direct correlation between Shwachman-Diamond syndrome and type 1 diabetes mellitus have been reported, therefore the presence of both diseases in the same patient might be a chance association, however we suggest that the defects in immune regulation of Shwachman-Diamond syndrome might play a role in the development of type 1 diabetes mellitus.
Keywords: Bone Marrow Diseases; CD4-CD8 Ratio; Diabetes Mellitus, Type 1; Exocrine Pancreatic Insufficiency; Female; Heterozygote; Humans; Immune System; Infant; Italy; Lipomatosis; Male; Mutation; Prevalence; Proteins; Registries

The significance of mannose-binding lectin gene polymorphisms on the risk of BK virus coinfection in women with human papillomavirus-positive cervical lesions. - Comar, Manola; Segat, Ludovica; Crovella, Sergio; Bovenzi, Massimo; Cortini, Enzo; Tognon, Mauro (Hum Immunol, 2011)
The simultaneous detection of oncogenic human papillomavirus (HPV) and BK virus (BKV) has been recently reported in cervical cancers, suggesting that these viruses may act together in the process of cell transformation; host genetic polymorphisms may also influence virus persistence/reactivation. To disclose a possible role of the gene encoding for the mannose-binding lectin, MBL2, in susceptibility to BKV infection, we analyzed functional polymorphisms in the first exon of MBL2 in women stratified for the presence/absence of BKV and affected by different grades of HPV-induced cervical precancerous lesions. All BKV-positive samples were also HPV positive (HPV 16), and all presented with high-grade squamous intraepithelial lesions. The MBL2 A allele was significantly more frequent in BKV-negative patients than in BKV-positive patients. These data indicate a possible role for the A allele in conferring protection to BKV infection in high-risk HPV-positive women (odds ratio 0.40, 95% confidence interval 0.20-0.85, p = 0.01).
Keywords: Adult; Aged; Alleles; BK Virus; Cervical Intraepithelial Neoplasia; Cervix Uteri; DNA Fingerprinting; DNA, Viral; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Human papillomavirus 16; Humans; Italy; Mannose-Binding Lectin; Odds Ratio; Papillomavirus Infections; Polymorphism, Genetic; Polyomavirus Infections; Risk; Viral Load

A singular case of congenital self-healing histiocytosis with skin, liver and atypical eye involvement. - Parentin, Fulvio; Ventura, Giovanna; Pastore, Serena; Kiren, Valentina; Bibalo, Chiara; Pensiero, Stefano; Lepore, Loredana (Ocul Immunol Inflamm, 2011)
PURPOSE: To describe a rare case of congenital self-healing Langerhans cell histiocytosis (CSHLCH) presenting with atypical eye involvement. DESIGN: Case report. METHODS: A female newborn presented with purpuric lesions over the trunk, limbs, and face. Liver ultrasonography revealed hypoechogenic lesions with blurred borders. Biomicroscopy showed right posterior synechiae with fibrinoid deposits on the lens. At 7 months she presented with right acute glaucoma. RESULTS: Biomicroscopy showed the presence of inflammatory pseudo-membrane covering the anterior surface of the lens, iris, and iridocorneal angle. Ab externo trabeculotomy was performed; access to the anterior chamber with capsulorrhexis forceps permitted a peeling of the pseudo-membrane with normalization of the intraocular pressure. Histologic examination of the membrane revealed an inflammatory tissue with CD1a and S-100 positive histiocytic cells. CONCLUSIONS: This is the first case of CSHLCH describing acute glaucoma secondary to a pseudo-inflammatory membrane with typical histiocytic cells, occluding the iridocorneal angle.
Keywords: Antigens, CD1; Convalescence; Female; Glaucoma; Histiocytosis, Langerhans-Cell; Humans; Infant; Intraocular Pressure; Iridocorneal Endothelial Syndrome; Liver Diseases; S100 Proteins; Skin Diseases; Trabeculectomy

Somatic mosaic IDH1 and IDH2 mutations are associated with enchondroma and spindle cell hemangioma in Ollier disease and Maffucci syndrome. - Pansuriya, Twinkal C; van Eijk, Ronald; d'Adamo, Pio; van Ruler, Maayke A J H; Kuijjer, Marieke L; Oosting, Jan; Cleton-Jansen, Anne-Marie; van Oosterwijk, Jolieke G; Verbeke, Sofie L J; Meijer, Daniëlle; van Wezel, Tom; Nord, Karolin H; et al. (Nat Genet, 2011)
Ollier disease and Maffucci syndrome are non-hereditary skeletal disorders characterized by multiple enchondromas (Ollier disease) combined with spindle cell hemangiomas (Maffucci syndrome). We report somatic heterozygous mutations in IDH1 (c.394C>T encoding an R132C substitution and c.395G>A encoding an R132H substitution) or IDH2 (c.516G>C encoding R172S) in 87% of enchondromas (benign cartilage tumors) and in 70% of spindle cell hemangiomas (benign vascular lesions). In total, 35 of 43 (81%) subjects with Ollier disease and 10 of 13 (77%) with Maffucci syndrome carried IDH1 (98%) or IDH2 (2%) mutations in their tumors. Fourteen of 16 subjects had identical mutations in separate lesions. Immunohistochemistry to detect mutant IDH1 R132H protein suggested intraneoplastic and somatic mosaicism. IDH1 mutations in cartilage tumors were associated with hypermethylation and downregulated expression of several genes. Mutations were also found in 40% of solitary central cartilaginous tumors and in four chondrosarcoma cell lines, which will enable functional studies to assess the role of IDH1 and IDH2 mutations in tumor formation.
Keywords: Adult; Case-Control Studies; Cell Line, Tumor; DNA Methylation; Enchondromatosis; Female; Gene Expression Profiling; Gene Expression Regulation; Genome-Wide Association Study; Humans; Isocitrate Dehydrogenase; Male; Middle Aged; Mosaicism; Mutation, Missense; Sequence Analysis, DNA; Transcription, Genetic; Young Adult

Splicing mutations in glycogen-storage disease type II: evaluation of the full spectrum of mutations and their relation to patients' phenotypes. - Zampieri, Stefania; Buratti, Emanuele; Dominissini, Silvia; Montalvo, Anna Lisa; Pittis, Maria Gabriela; Bembi, Bruno; Dardis, Andrea (Eur J Hum Genet, 2011)
Glycogen-storage disease type II is an autosomal recessive-inherited disorder due to the deficiency of acid α-glucosidase. A large number of mutations in the acid α-glucosidase gene have been described to date. Among them, ~15% are variations that may affect mRNA splicing process. In this study, we have for the first time comprehensively reviewed the available information on splicing mutations of the acid α-glucosidase gene and we have evaluated their possible impact on the splicing process using different in silico approaches. Out of the 39 different GAA-sequence variations described, an in silico analysis using seven different programs showed that 97% of them are predicted to have an impact on the splicing process. Moreover, this analysis showed a quite good correlation between the impact of the mutation on the splicing process and the clinical phenotype. In addition, we have performed the functional characterization of three novel sequence variants found in Italian patients and still uncharacterized. Using a minigene system, we have confirmed their pathogenic nature. In conclusion, this study has shown that in silico analysis represents a useful tool to select mutations that affect the splicing process of the acid α-glucosidase gene and provides an updated picture of all this kind of mutations reported till now.
Keywords: alpha-Glucosidases; Cell Line; Computational Biology; DNA Mutational Analysis; Exons; Glycogen Storage Disease Type II; Humans; Introns; Mutagenesis, Site-Directed; Mutation; Phenotype; RNA Splicing

Successful treatment of acne with isotretinoin in chronic granulomatous disease. - Barbi, Egidio; Berti, Irene; Minute, Marta; Zennaro, Floriana (Eur J Dermatol, 2011)
Keywords: Acne Vulgaris; Adult; Anti-Infective Agents; Comorbidity; Dermatologic Agents; Granulomatous Disease, Chronic; Humans; Isotretinoin; Male; Trimethoprim-Sulfamethoxazole Combination

Screening for GJB2 and GJB6 gene mutations in patients from Campania region with sensorineural hearing loss. - Chinetti, Viviana; Iossa, Sandra; Auletta, Gennaro; Laria, Carla; De Luca, Maria; Di Leva, Francesca; Riccardi, Pasquale; Giannini, Pasquale; Gasparini, Paolo; Ciccodicola, Alfredo; Marciano, Elio; Franzè, Annamaria (Int J Audiol, 2010)
The aim of this study was to screen 349 patients affected by sensorineural hearing loss (SNHL), mostly from the Campania region (southern Italy), for GJB2 gene mutations and for two deletions of the GJB6 gene (del GJB6 -D13S1830 and del GJB6 -D13S1854). We identified pathogenetic GJB2 mutations in 51 cases (15% of patients). No GJB6 mutation was found. We also examined the audiologic features of the patients for whom we had an etiologic diagnosis, in order to identify correlations between the severity of hearing loss and the type of mutation.
Keywords: Acoustic Stimulation; Adolescent; Adult; Audiometry; Auditory Perception; Child; Child, Preschool; Connexins; Genetic Predisposition to Disease; Genetic Testing; Hearing Loss, Sensorineural; Heterozygote; Homozygote; Humans; Italy; Mass Screening; Middle Aged; Mutation; Phenotype; Risk Factors; Severity of Illness Index; Young Adult

Severe X-linked mitochondrial encephalomyopathy associated with a mutation in apoptosis-inducing factor. - Ghezzi, Daniele; Sevrioukova, Irina; Invernizzi, Federica; Lamperti, Costanza; Mora, Marina; d'Adamo, Pio; Novara, Francesca; Zuffardi, Orsetta; Uziel, Graziella; Zeviani, Massimo (Am J Hum Genet, 2010)
We investigated two male infant patients who were given a diagnosis of progressive mitochondrial encephalomyopathy on the basis of clinical, biochemical, and morphological features. These patients were born from monozygotic twin sisters and unrelated fathers, suggesting an X-linked trait. Fibroblasts from both showed reduction of respiratory chain (RC) cIII and cIV, but not of cI activities. We found a disease-segregating mutation in the X-linked AIFM1 gene, encoding the Apoptosis-Inducing Factor (AIF) mitochondrion-associated 1 precursor that deletes arginine 201 (R201 del). Under normal conditions, mature AIF is a FAD-dependent NADH oxidase of unknown function and is targeted to the mitochondrial intermembrane space (this form is called AIF(mit)). Upon apoptogenic stimuli, a soluble form (AIF(sol)) is released by proteolytic cleavage and migrates to the nucleus, where it induces "parthanatos," i.e., caspase-independent fragmentation of chromosomal DNA. In vitro, the AIF(R201 del) mutation decreases stability of both AIF(mit) and AIF(sol) and increases the AIF(sol) DNA binding affinity, a prerequisite for nuclear apoptosis. In AIF(R201 del) fibroblasts, staurosporine-induced parthanatos was markedly increased, whereas re-expression of AIF(wt) induced recovery of RC activities. Numerous TUNEL-positive, caspase 3-negative nuclei were visualized in patient #1's muscle, again indicating markedly increased parthanatos in the AIF(R201 del) critical tissues. We conclude that AIF(R201 del) is an unstable mutant variant associated with increased parthanatos-linked cell death. Our data suggest a role for AIF in RC integrity and mtDNA maintenance, at least in some tissues. Interestingly, riboflavin supplementation was associated with prolonged improvement of patient #1's neurological conditions, as well as correction of RC defects in mutant fibroblasts, suggesting that stabilization of the FAD binding in AIF(mit) is beneficial.
Keywords: Apoptosis; Apoptosis Inducing Factor; Caspase 3; Computer Simulation; Dietary Supplements; DNA Primers; DNA, Mitochondrial; Electron Transport; Female; Fibroblasts; Flavin-Adenine Dinucleotide; Genes, X-Linked; Humans; In Situ Nick-End Labeling; Infant, Newborn; Magnetic Resonance Imaging; Male; Mitochondrial Encephalomyopathies; Muscle, Skeletal; Mutation; Nervous System Diseases; Pedigree; Poly(ADP-ribose) Polymerases; Protein Conformation; Riboflavin; Staurosporine; Twins, Monozygotic

Splenomegaly as presentation of a wandering spleen. - Maschio, Massimo; Cozzi, Giorgio; Sanabor, Daniela; Zennaro, Floriana; Gloria, Pelizzo; Barbi, Egidio (J Pediatr, 2010)
Keywords: Child; Female; Humans; Splenomegaly; Wandering Spleen

State of the art and recommendations. Kangaroo mother care: application in a high-tech environment. - Nyqvist, K H; Anderson, G C; Bergman, N; Cattaneo, A; Charpak, N; Davanzo, R; Ewald, U; Ludington-Hoe, S; Mendoza, S; Pallás-Allonso, C; Peláez, J G; Sizun, J; et al. (Breastfeed Rev, 2010)
UNLABELLED: Since Kangaroo Mother Care (KMC) was developed in Colombia in the 1970s, two trends in clinical application emerged. In low-income settings, the original KMC modelis implemented. This consists of continuous (24 h/day; 7 days/week) and prolonged mother/parent-infant skin-to-skin contact; early discharge with the infant in the kangaroo position; (ideally) exclusive breastfeeding and, adequate follow up. In affluent settings, intermittent KMC with sessions of one or a few hours skin-to-skin contact for a limited period is common. As a result of the increasing evidence of the benefits of KMC for both infants and families in all intensive care settings, KMC in a high-tech environment was chosen as the topic for the first European Conference on KMC, and the clinical implementation of the KMC modelin all types of settings was discussed at the 7th International Workshop on KMC Kangaroo Mother Care protocols in high-tech Neonatal Intensive Care Units (NICU) should specify criteria for initiation, kangaroo position, transfer to/from KMC, transport in kangaroo position, kangaroo nutrition, parents'role, modification of the NICU environment, performance of care in KMC, and KMCin case of infant instability. CONCLUSION: Implementation of the original KMC method, with continuous skin-to-skin contact whenever possible, is recommended for application in high-tech environments, although scientific evaluation should continue.

State of the art and recommendations. Kangaroo mother care: application in a high-tech environment. - Nyqvist, K H; Anderson, G C; Bergman, N; Cattaneo, A; Charpak, N; Davanzo, R; Ewald, U; Ludington-Hoe, S; Mendoza, S; Pallás-Allonso, C; Peláez, J G; Sizun, J; et al. (Acta Paediatr, 2010)
UNLABELLED: Since Kangaroo Mother Care (KMC) was developed in Colombia in the 1970s, two trends in clinical application emerged. In low income settings, the original KMC model is implemented. This consists of continuous (24 h/day, 7 days/week) and prolonged mother/parent-infant skin-to-skin contact; early discharge with the infant in the kangaroo position; (ideally) exclusive breastfeeding; and, adequate follow-up. In affluent settings, intermittent KMC with sessions of one or a few hours skin-to-skin contact for a limited period is common. As a result of the increasing evidence of the benefits of KMC for both infants and families in all intensive care settings, KMC in a high-tech environment was chosen as the topic for the first European Conference on KMC, and the clinical implementation of the KMC model in all types of settings was discussed at the 7th International Workshop on KMC. Kangaroo Mother Care protocols in high-tech Neonatal Intensive Care Units (NICU) should specify criteria for initiation, kangaroo position, transfer to/from KMC, transport in kangaroo position, kangaroo nutrition, parents' role, modification of the NICU environment, performance of care in KMC, and KMC in case of infant instability. CONCLUSION: Implementation of the original KMC method, with continuous skin-to-skin contact whenever possible, is recommended for application in high-tech environments, although scientific evaluation should continue.
Keywords: Attitude of Health Personnel; Female; Humans; Infant Care; Infant, Newborn; Intensive Care Units, Neonatal; Male; Parent-Child Relations; Practice Guidelines as Topic; Professional-Patient Relations; Role; Skin; Visitors to Patients

Storage of human milk: accepting certain uncertainties. - Davanzo, Riccardo; Travan, Laura; Demarini, Sergio (J Hum Lact, 2010)
Keywords: Food Handling; Humans; Milk, Human; Refrigeration

[Strategies for cardiovascular prevention in children]. - Spinelli, Angela; Nardone, Paola; Lamberti, Anna; Baglio, Giovanni (G Ital Cardiol (Rome), 2010)
Keywords: Body Mass Index; Cardiovascular Diseases; Child; Diet, Mediterranean; Food Habits; Humans; Life Style; Motor Activity; Obesity; Overweight; Patient Education as Topic; Population Surveillance; Questionnaires; Risk Factors

Structural aspects of plant antimicrobial peptides. - Padovan, Lara; Scocchi, Marco; Tossi, Alessandro (Curr Protein Pept Sci, 2010)
Antimicrobial peptides exert an important role in plant defence and their structure/activity relationship against pathogens is widely described. Although the most striking feature of these antimicrobial peptides is their molecular diversity, they share some common features, such as a relatively low molecular weight, and the presence of a variable number of cysteines residues that contribute to stabilize conserved scaffolds through disulphide bond formation, and can be assigned to different structural classes. Peptides from different classes in some cases act synergistically against pathogens when produced by the same tissue, and contribute to extending defence to a wider range of microbes. In this review we briefly describe the structure of some of the main plant antimicrobial peptide classes: thionins, defensins, lipid transfer proteins, cyclotides and snakins, and how they are reported to contribute to the plant protection. In many cases these antimicrobial peptides show a wider activity spectrum than that suggested by their name, exerting an action also against predatory insects and revealing useful antiviral activities. This extends their interest from defense of important food crops also to the design of novel anti-infective compounds for both pharmaceutical and agricultural applications.
Keywords: Amino Acid Sequence; Antimicrobial Cationic Peptides; Molecular Sequence Data; Plant Proteins; Plants; Sequence Alignment

Studies of oxygen binding energy to hemoglobin molecule. - Chow, Y W; Pietranico, R; Mukerji, A (Biochem Biophys Res Commun, 1975)
Keywords: Binding Sites; Cobalt; Hemoglobins; Humans; Hydrogen-Ion Concentration; Iron; Ligands; Mathematics; Oxygen; Oxyhemoglobins; Protein Binding; Spectrum Analysis